Embodiment of Dramatic Contradicted-Power Conflict in Faqe Tayran’s Epic Poem “Shekhe San’an - Man vs. self, man vs. man as a simple - - Hassan, Shivan Q.; Khaled, Abdullah A. (Humanities Journal of University of Zakho, 2018)
Faqe Tayran’s epic of Shekhe San’an, as an epic of Kurdish classic literature, has a lot of dramatic characteristics via which the bases of many dramatic techniques and types can be identified. Dramatic conflict which is regarded as the essence of drama without which the dramatic text loses its effectiveness, interest and taste and is dull. The dramatic nature of this epic allows one to be able to handle it as a dramatic text, especially because the dramatic conflict is powerfully manifested in this epic. Dramatic conflict according to its nature, concept and state is divided into some types: the general one, the concept of embodied conflict, the type of conflict and antagonism. In this study, antagonism is adopted because this type of dramatic conflict is in conformity with the nature and content of this epic more than do the other types. Therefore, this study is entitled "Embodiment of Dramatic Contradicted-Power Conflict in Faqe Tayran’s Epic Poem “Shekhe San’an - Man vs. self, man vs. man as a simple –"